2015
DOI: 10.1016/j.cell.2015.10.031
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Calcium and SOL Protease Mediate Temperature Resetting of Circadian Clocks

Abstract: Summary Circadian clocks integrate light and temperature input to remain synchronized with the day/night cycle. Although light input to the clock is well studied, the molecular mechanisms by which circadian clocks respond to temperature remain poorly understood. We found that temperature phase-shifts Drosophila circadian clocks through degradation of the pacemaker protein TIM. This degradation is mechanistically distinct from photic CRY-dependent TIM degradation. Thermal TIM degradation is triggered by cytosol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 73 publications
0
16
0
1
Order By: Relevance
“…S3) have failed to find this effect, and subsequent work by other groups has cast doubt on the role of cryptochrome in circadian temperature entrainment (57,58). New data from the laboratory of Patrick Emery (39) suggest that calcium signaling is essential for circadian temperature responses and that the above-mentioned neural pathways converge by calciumdependent degradation of TIM.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S3) have failed to find this effect, and subsequent work by other groups has cast doubt on the role of cryptochrome in circadian temperature entrainment (57,58). New data from the laboratory of Patrick Emery (39) suggest that calcium signaling is essential for circadian temperature responses and that the above-mentioned neural pathways converge by calciumdependent degradation of TIM.…”
Section: Resultsmentioning
confidence: 99%
“…S4) suggest that separate mechanisms are present for hot and cold responses even with Drosophila. New data from the laboratory of Patrick Emery (39) suggest that the various neural pathways involved in circadian temperature signaling all act via calcium-dependent degradation of TIM through the SOL protease pathway. The data show that inhibiting calcium signaling significantly reduces circadian phase shifts in response to temperature changes and, most interestingly, that the calcium response to a temperature step appears to be adaptive, just as our model predicts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the roles of calpains in lipid metabolism have not been clarified in Drosophila, the proteolytic activity of calpain A is shown to be enhanced by phosphatidylinositol 4,5-bisphosphate, phosphatidylinositol 4-monophosphate, phosphatidylinositol, and phosphatidic acid (32). Recently, it was also reported that SOL mediates temperature reset of the circadian clock (33), anticipating the participation of calpain in the temperature-sensitive regulation of membrane fluidity. Therefore, it is plausible that calpains are involved in the regulation of DESAT1 expression that modulates phospholipid composition and lipid membrane fluidity.…”
Section: Role Of Di-proline Motif In ⌬9-desaturase Degradationmentioning
confidence: 99%
“…These physiological rhythms, in turn, can serve as reinforcing feedback to both the SCN (non-photic cues) and to the CNS and local targets (Balsalobre et al, 2000;Buhr et al, 2010;Stokkan et al, 2001;Tataroglu et al, 2015). Under this model, the phase relations between the SCN and peripheral targets are generally regarded as hard-wired and rigid, ensuring the rhythms are accurately timed relative to the light-dark cycle.…”
Section: Temporal Niche Switchingmentioning
confidence: 99%